Comprehensive Evaluation and Trade‐Off of Top‐Level Requirements for BWB UAVs - Xinshi Suo; Zhouwei Fan; Yundong Guo; Tengzhou Xu (Engineering Reports, 2025)
ABSTRACT To enhance the rationality of top‐level requirement development for Blended Wing Body (BWB) Unmanned Aerial Vehicles (UAVs), a top‐level requirement trade‐off process is established to transform the requirement trade‐off into an evaluation and optimization procedure during the pre‐conceptual design phase. Given the distinct geometric and performance characteristics inherent to BWB UAVs, a hybrid methodology integrating numerical simulations and empirical estimations is utilized to holistically assess geometry, weight, aerodynamics, flight performance, and stealth capabilities. Four critical criteria—cost‐effectiveness, payload capacity, flight performance, and stealth capability—are applied to identify seven representative top‐level requirements, which are subsequently integrated into a comprehensive evaluation model. A parallelizable subset‐simulation optimization algorithm is implemented to iteratively refine the design, thereby maximizing overall system competitiveness. The optimal design improves the competitiveness of the top‐level requirements by 46.8% compared to the baseline design, validating the feasibility of the proposed method.